Apostolic Legates in Poland in the Middle Ages and Their Role in Adopting Particular Ecclesiastical Legislation by the Polish Church – Educational Aspects - Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2018)
The official reception of the conciliar legislation in medieval Poland was greatly influenced by the papal legates, ambassadors endowed with papal authority, who brought conciliar canons to the country ruled at the time by the Piasts and made them public at councils convened with the participation of papal legates, closely monitored the observance of Canon Law and its scope expansion, concurred statutes of Polish provincial and diocesan councils, approved or rejected nominations of bishops, etc. They also acted as intermediaries in personal interventions of popes in their involvement in the functioning of the Church in Poland. Their duties also included inspections in dioceses. Visits of papal legates in Poland were relatively frequent and their main goal was to enforce and implement ecclesiastical reforms in the country. In some instances, a strict relationship between a stay of a papal representative in Poland and the process of the creation and spread of schools is clearly observable. The article examines source accounts concerning the visits of papal legates in Poland, as well as analyses the available statues of legate councils in terms of the provisions included in them regarding education of representatives of the clergy and laymen alike.